Explanatory factors for the rapid decline in fertility in the Brazilian Semi-arid region - Silva, Everlane Suane de Araújo da; Paes, Neir Antunes; Silva, Arthur Antônio Farias de Barros e (Brazilian Journal of Biometrics, 2022)
In recent decades, Brazil has experienced an accelerated reduction in fertility levels, reaching an average of 1.8 children per woman in the reproductive period in 2015, an effect that has reached one of the most vulnerable regions in Latin America: the Brazilian Semiarid region. The objective was to identify which demographic, socioeconomic and health factors influenced the reduction of fertility levels in the 1,262 municipalities that make up the Brazilian Semiarid Region, in the period 1991-2010. The application of the panel data regression model showed that the reduction in Gini Index, illiteracy rate, and increase in life expectancy, aging rate significantly contributed to the decrease in fertility levels in the Semiarid region. The results indicated that the fertility levels converged in the period towards a regional homogenization close to the replacement level, which declined at a faster pace than the improvement in the region’s development levels.